2016
DOI: 10.1111/jcpt.12410
|View full text |Cite
|
Sign up to set email alerts
|

Network meta-analysis of Chinese herb injections combined with FOLFOX chemotherapy in the treatment of advanced colorectal cancer

Abstract: Summary What is known and Objective Research has indicated that some Chinese herb injections (CHIs) might be beneficial in combination with chemotherapy, including remedies that might be used as effective chemosensitizers and radiosensitizers, or as palliative therapy. Here, we carried out a network meta‐analysis to assess the clinical efficacy and safety of CHIs combined with oxaliplatin, 5‐fluorouracil and leucovorin (FOLFOX) for advanced colorectal cancer (CRC). Methods PubMed, EMBASE.com, the Cochrane Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
(14 reference statements)
0
12
1
1
Order By: Relevance
“…Neurotoxicity is a frequent adverse effect of cancer chemotherapy and radiotherapy, and causes excruciating pain to cancer patients. A network meta-analysis shows that Ai-Di, Shen-Qi-Fu-Zheng, and Matrine injections approved by the Food and Drug Administration of China, improve the overall response rate and quality of life, and reduce the incidence of peripheral neurotoxicity (III-IV) for advanced colorectal cancer treated with oxaliplatin, 5-fluorouracil, and leucovorin (Ge et al, 2016 ). Traditional Japanese medicine Goshajinkigan (TJ107) is used to alleviate neuropathy and general pain.…”
Section: Need To Clarify the Prevention Of Neurotoxicitymentioning
confidence: 99%
“…Neurotoxicity is a frequent adverse effect of cancer chemotherapy and radiotherapy, and causes excruciating pain to cancer patients. A network meta-analysis shows that Ai-Di, Shen-Qi-Fu-Zheng, and Matrine injections approved by the Food and Drug Administration of China, improve the overall response rate and quality of life, and reduce the incidence of peripheral neurotoxicity (III-IV) for advanced colorectal cancer treated with oxaliplatin, 5-fluorouracil, and leucovorin (Ge et al, 2016 ). Traditional Japanese medicine Goshajinkigan (TJ107) is used to alleviate neuropathy and general pain.…”
Section: Need To Clarify the Prevention Of Neurotoxicitymentioning
confidence: 99%
“…Aidi injection (CFDA approval number, Z52020236) is an anti-tumor Chinese medicine from the spotted jellyfish, A. membranaceus , Acanthopanax, and ginseng (Xiao et al, 2017 ). Aidi injections can reportedly alleviate side effects of chemotherapeutics and exert an adjuvant effect on the comprehensive treatment of DSM (Wang T. et al, 2014 ; Ge et al, 2016 ). In a meta-analysis of 32 RCTs by Wang et al, Aidi injections combined with chemotherapeutics improved the effective rate of chemotherapeutics for gastric cancer and the patient's quality of life, and decreased incidences of side effects such as nausea and vomiting, diarrhea, leukopenia III–IV, and thrombocytopenia III–IV (Jiancheng et al, 2015 ).…”
Section: Chinese Medicine Preparations For Dsmmentioning
confidence: 99%
“…Because of its potential for preventing and treating cancer, TCM has received wide attention from around the world, including Western countries. Many studies found that TCM combined with radiotherapy or chemotherapy for malignant tumors could significantly reduce the incidence of adverse reactions to radiotherapy or chemotherapy and improve cellular immunity and quality of life for patients (Qi et al, 2010 ; Ge et al, 2016 ; Liu et al, 2016a , b ). Even some TCM preparations have a synergistic effect on chemotherapy, which can both prolong patient survival and reduce tumor recurrence and metastasis (Tian et al, 2012a ; Pandey et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has become a standard regimen for CRC both as adjuvant therapy and as treatment for metastatic cancer, the response to oxaliplatin-based chemotherapy still varied wildly among individuals in clinical practice. The reported overall response rate was 40% in advanced CRC 3. Studies in human CRC cell lines confirmed that multiple factors are involved in the oxaliplatin resistance and clinical prognosis including decreased drug accumulation and enhanced capacity to repair and tolerate DNA damage 4,5.…”
Section: Introductionmentioning
confidence: 96%